Metody i efekty ograniczania emisji CO2 – porównanie rozwiązań stosowanych w Unii Europejskiej i wybranych państwach - Nadolny, Łukasz (Gospodarka w Praktyce i Teorii, 2013)
The main goal of this article is to show methods of greenhouse gases reduction introduced in European Union and four other countries: China, USA, Russia and India. All together they are the top five economies responsible for over a 65% of carbon dioxide global emission. Each country or union has developed its own way of coping with a problem of global warming. Does their governments really try to stop polluting the atmosphere, or maybe they just want to achieve different goals? How efficient are their methods? The last part of the article consist of data analysis showing how high the levels of CO2 emissions have been since 1980 till 2011. It gives a reader a picture of each country’s impact on global warming and theirs results in reducing it.